Telepsychotherapy During the COVID-19 Pandemic: The Experience of Lebanese Mental Health Professionals - Tohme, Pia (2021)
The COVID-19 pandemic has taken the mental health system by surprise, with the state of lockdown forcing businesses to close their doors, including many mental health services. This has driven many psychotherapists and other mental health professionals towards telepsychotherapy, relying on online consultations to provide continuity of care. However, the adoption of telepsychotherapy required major adaptations from both mental health professionals and patients. This study set out to explore the predictors of the use of online consultations and the perceived level of comfort using telepsychotherapy in a sample of 73 Lebanese mental health professionals. Data was collected via online dissemination of a survey. Results show that 82% of participants made use of online consultations in the past few days, reflecting the adaptation of Lebanese mental health professionals to the atypical newly imposed situation triggered by the COVID-19 pandemic and its consequent lockdown. Having previous experience in the use of online consultations and perceived level of telepresence were significant predictors of the level of comfort of mental health professionals in the execution online consultations. We suggest that more awareness and trainings are required around the practice of telepsychotherapy outside the context of the COVID-19 pandemic.